ANALYSIS OF INCOME AND LIFESTYLE ON PUBLIC CONSUMPTION IN THE PERSPECTIVE OF ISLAMIC ECONOMICS - Budiman, Ary A; Irwan, Muhammad; Hidayat, Ali Akbar (Journal of Finance, Economics and Business, 2025)
This study aims to analyse the effect of income and lifestyle on community consumption. The population in this study were the people of Selaparang District, Mataram City with a sample of 100 respondents using purposive sampling technique with criteria aged 25-50 years. this research uses quantitative methods. The data analysis used in this study is multiple linear regression test, with the help of SPSS software version 24. Based on the partial test results, it shows that the income variable has a positive and significant effect on consumption, and the lifestyle variable has a positive and significant effect on consumption. While the simultaneous test shows that income and lifestyle have a positive and significant effect on community consumption in Selaparang sub-district, Mataram City. The coefficient of determination of 0.398 or 39.80 per cent indicates that income and lifestyle affect consumption by 39.80 per cent and the rest is influenced by other variables.